2018
DOI: 10.2298/fuace160514001b
|View full text |Cite
|
Sign up to set email alerts
|

Torsional behaviour of normal strength RCC beams with ferrocement “U” wraps

Abstract: Wrapping technology is one of the effective ways of strengthening concrete elements. Several researchers reported the effectiveness of Glass fiber reinforced polymers and carbon fiber reinforced polymers for improving the strength of the concrete elements. Wrapping on three sides is one of the effective methods for strengthening the beams supporting slabs. Scant literature is available on the strength enhancement of ?U? wrapped concrete elements subjected to torsional loads. In this investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…The torsional behavior of beams can be modeled using finite element analysis or experimental testing. The torque-twist responses of normal-strength concrete beams with ferrocement "U" wrap (plain beams and reinforced concrete beams) with various types were tested and analyzed [23].…”
Section: Torsional Behavior Of Normal-strength Beamsmentioning
confidence: 99%
“…The torsional behavior of beams can be modeled using finite element analysis or experimental testing. The torque-twist responses of normal-strength concrete beams with ferrocement "U" wrap (plain beams and reinforced concrete beams) with various types were tested and analyzed [23].…”
Section: Torsional Behavior Of Normal-strength Beamsmentioning
confidence: 99%
“…Few analytical and experimental studies are found which quantify the torsional strength of FRP bonded full wrap [8][9]. But inaccessibility and extension of flanges over the web has necessitated strengthening the beams by "U" wrap rather than full wrapping [10]. Methods for quantification of torsional strength of "U" wrapped beams are found to be very few [11].…”
Section: Necessity Of Present Investigationmentioning
confidence: 99%
“…An analytical model was developed using skew bending theory with modifications to the material properties. The detailed procedure was presented by Behera et al [10][11][12][13].…”
Section: Analytical Modelmentioning
confidence: 99%
“…Torsion is a supreme aspect which is considered along with other basic structural actions. The torsional effects cannot be ignored in the present-day design due to (I) Large torsional moments tempted in structures and (II) Critical safety features used in project methods [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Concrete Structures Are Imperiled To Basic Structuralmentioning
confidence: 99%